Tracing the Importance of Mother Blame - Shankar, Irene (Atlantis, 2026)
During a health crisis, vaccines can curb the spread of diseases and provide much-needed immunity for all those deemed at risk. To reach herd immunity and successfully curb disease spread, a significant portion of the population needs to get vaccinated. Thus, it is vital to consider the conditions under which people will accept or refuse vaccinations. Using a case study from the 2009 H1N1 pandemic, this paper examines how historical cases of iatrogenesis, medical intervention on women’s bodies, societal practices of blaming mothers for children’s ill health, and the provincial government’s record on healthcare funding and support worked together to inform women’s vaccination decisions. The findings, based on 19 qualitative semi-structured interviews, indicate that during the 2009 H1N1 pandemic, pregnant women were concerned about making the wrong decisions due to societal mothering blame and gendered responsibility within the field of medicine. Their decision to get vaccinated was made in consideration of medical surveillance and scrutiny of pregnant bodies and their feelings of (dis)trust in the provincial government. The research findings allow for a more complex understanding of health decisions by situating women’s vaccination decisions within a larger historical and sociopolitical context. Moreover, the findings indicate that trust cannot be readily invoked in moments of crisis but requires a sustained and ongoing dedication to examining issues of gender inequity within medical practices and governmental policies.